A rare case of cervical facet joint and synovial cyst at C5/C6. (July 2016) - Phan, Kevin; Mobbs, Ralph J.
Highlights: Cervical synovial facet joint cysts are extremely rare. A 40-year-old woman presented with pain in the C6 dermatome. MRI confirmed a cervical synovial cyst at C5/C6. Posterior decompressive laminotomy and cyst excision was carried out. After complete facetectomy, fusion was carried out for stability. Abstract: Lumbar synovial cysts are uncommon, and particularly rare at cervical levels. We report a 40-year-old woman who presented with pain distribution in the typical C6 dermatome. MRI revealed a right-sided large extradural cystic lesion adjacent to the C5/C6 facet joint that was hyperintense on T2-weighted MRI and hypointense on T1-weighted MRI. The patient underwent posterior cervical surgery at the C5/C6 level which involved posterior decompressive unilateral laminotomy and excision of the C5/C6 facet joint cyst. Following complete facetectomy of the right C5/C6 facet joint and exposure of the C6 nerve throughout its foraminal course, instrumented fusion was performed. Following the procedure, the patient had an uneventful recovery with relief of her radicular symptoms at follow-up clinical review.